2017
DOI: 10.1177/1440783317705204
|View full text |Cite
|
Sign up to set email alerts
|

Youth homelessness: A social justice approach

Abstract: Social justice approaches that work towards eliminating youth homelessness with a sole focus on material needs overlook the significance of non-material aspects, such as the impact of social exclusion and stigma on individuals' subjectivities. The lack of social legitimacy associated with homelessness is exacerbated under neoliberal conditions, with the shift from social to individual responsibility positioning those unable to achieve the normative transition to adulthood as social failures. We draw on intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The unpredictability, chronicity, and graveness that commonly characterize the experience of homelessness are likely to pose profound challenges to the effective coping with, and recovery from, SMI (Padgett et al, 2012;Yanos, 2007;Klitzing, 2003;Gottlieb, 1997). Several lines of research have demonstrated the profoundly negative effects of extreme poverty and homelessness on vital enablers of positive coping, including mental health recovery (Kirkpatrick & Byrne, 2009), a positive self-concept (Padgett, 2007), social connectedness (Padgett et al, 2008), hope (Kirst et al, 2014), self-esteem, and self-efficacy (Watson & Cuervo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The unpredictability, chronicity, and graveness that commonly characterize the experience of homelessness are likely to pose profound challenges to the effective coping with, and recovery from, SMI (Padgett et al, 2012;Yanos, 2007;Klitzing, 2003;Gottlieb, 1997). Several lines of research have demonstrated the profoundly negative effects of extreme poverty and homelessness on vital enablers of positive coping, including mental health recovery (Kirkpatrick & Byrne, 2009), a positive self-concept (Padgett, 2007), social connectedness (Padgett et al, 2008), hope (Kirst et al, 2014), self-esteem, and self-efficacy (Watson & Cuervo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, there are two schools of thought that seek to explain the issue of housing and homelessness, namely, the risk discourse and the structural discourse. Whereas the risk discourse focuses on individual actions in the creation and maintenance of homelessness, the structural discourse focuses on how broader structures of dominance influence incidences of homelessness among various groups of people (Gerrard 2015;Kuskoff, 2018;Kelly, 2001;Mullaly, 2007;Watson and Cuervo 2017). Over the years, different approaches to ending homelessness have been suggested in various disciplines of public policy, sociology, social work, medicine, women's studies and urban planning.…”
Section: 2mentioning
confidence: 99%
“…Over the years, different approaches to ending homelessness have been suggested in various disciplines of public policy, sociology, social work, medicine, women's studies and urban planning. Most notably is the neoliberal govermentality approach (Kelly 2001) and the critical discourse analysis 7 approach (Fairclough,Mulderrig & Wodak, 2011), which encompasses the structural approach (Mullay, 2007) and the social justice approach (Watson & Cuervo 2017).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Homelessness is a complex phenomenon (Singh, Koiri & Shukla, 2018;Watson & Cuervo, 2017) with no singular definition, largely because of the diversity of contexts that homeless people face (Eissmann & Takeuchi, 2020). However, both academics and policymakers concur on three broad categories of homelessness, namely primary, secondary and tertiary homelessness.…”
Section: Introductionmentioning
confidence: 99%